2008
DOI: 10.1095/biolreprod.108.071407
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Conjugating Enzyme UBE2D2 Is Responsible for FBXW2 (F-Box and WD Repeat Domain Containing 2)-Mediated Human GCM1 (Glial Cell Missing Homolog 1) Ubiquitination and Degradation1

Abstract: Glial cell missing homolog 1 (GCM1) is an important transcription factor regulating placental cell fusion. Recently, we have demonstrated that GCM1 is a labile protein and that the F-box protein FBXW2 (F-box and WD repeat domain containing 2) mediates GCM1 ubiquitination for proteasomal degradation. Multiple factors are involved in the ubiquitin-proteasome degradation system. Therefore, in order to better understand the mechanism regulating GCM1 stability, we further isolated and characterized the E2 ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Here we showed that SKP2 is a novel substrate of FBXW2 with following lines of supporting evidence: (1) FBXW2 binds to SKP2 under physiological conditions; (2) FBXW2-SKP2 binding is dependent on an evolutionarily conserved FBXW2 putative consensus binding motif ( TS ELL S ) on SKP2; (3) FBXW2 overexpression reduces SKP2 levels by shortening its protein half-life; (4) FBXW2 depletion increases SKP2 levels by extending its protein half-life; (5) FBXW2, but not its FBXW2ΔF mutant, promotes ubiquitylation and subsequent degradation of SKP2; (6) FBXW2 mediated negative regulation of SKP2 is independent of CDH1. At the present time, the only known substrate of FBXW2 is GCM1 (Glial cell missing homolog 1)6768, a transcription factor that regulate placental development6970 without any known implication in cancer. Identification of SKP2 as a novel substrate of FBXW2 extended the list of FBXW2 substrates and revealed its biological function in human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that SKP2 is a novel substrate of FBXW2 with following lines of supporting evidence: (1) FBXW2 binds to SKP2 under physiological conditions; (2) FBXW2-SKP2 binding is dependent on an evolutionarily conserved FBXW2 putative consensus binding motif ( TS ELL S ) on SKP2; (3) FBXW2 overexpression reduces SKP2 levels by shortening its protein half-life; (4) FBXW2 depletion increases SKP2 levels by extending its protein half-life; (5) FBXW2, but not its FBXW2ΔF mutant, promotes ubiquitylation and subsequent degradation of SKP2; (6) FBXW2 mediated negative regulation of SKP2 is independent of CDH1. At the present time, the only known substrate of FBXW2 is GCM1 (Glial cell missing homolog 1)6768, a transcription factor that regulate placental development6970 without any known implication in cancer. Identification of SKP2 as a novel substrate of FBXW2 extended the list of FBXW2 substrates and revealed its biological function in human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…27 As a syncytialization-promoting molecule, GCM1 is required for the differentiation of the human trophoblast. 28 Previously, an interesting study by Chen and coworkers 29 found that GCM1 is a direct target for CUL1, and the CUL1–SCF complex mediates ubiquitination and degradation of human GCM1. In this study, GCM1 mRNA was upregulated after CUL1 siRNA transfection in primary cultured term CTB cells, suggesting a non-ubiquitination-related role of CUL1 on GCM1, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…8, 9 Furthermore, in vitro studies support a mechanistic relevance of post-translational GCM1 modifications for syncytiotrophoblast formation. 26, 27 However, physiological regulators of post-translational GCM1 modifications and their relevance in human placental diseases remain largely unknown. We demonstrate that expression of p45 NF-E2, which regulates both GCM1 acetylation and sumoylation, is closely related to the post-translational modification of GCM1 in human placentae without or with IUGR.…”
Section: Discussionmentioning
confidence: 99%